Persuasive leadership through framing, rhetoric, and history: An analysis of Zelensky’s speeches after the invasion of Ukraine - Marín-Albaladejo, Juan Antonio; Arroyas Langa, Enrique; Pérez-Díaz, Pedro Luis (Estudios sobre el Mensaje Periodístico, 2025)
Political communication is a key element at crucial moments in history to influence governments and public opinion in allied countries. The speeches of Ukraine’s president, Volodymyr Zelensky, have played an important role in his communicative strategy to try to maintain and increase the support of other states for his country in the war against Russia. This research analyzes the speeches he addressed to parliaments and citizens of different nations in the first two months after the beginning of the invasion of Ukraine on February 24, 2022. Based on a qualitative methodology that reconstructs the structure of the frames and identifies the rhetorical devices present in 27 complete speeches of the Ukrainian leader, the results reveal the predominance of four frames that associate the war with a clash of two antagonistic moral models that make any kind of equidistance impossible, and the existence of a threat to global security to which the international community cannot remain indifferent. To reinforce the persuasive effectiveness of his arguments and emphasize the need for the different measures he proposes, Zelensky uses historical analogies as a key symbolic mechanism in all the speeches analyzed, so that references to the legacy of memory facilitate the assimilation of his ideas by the public opinions of each society.
Keywords: Political communication; political leadership; framing; historical analogy; russo-ukrainian war